Mechanistic relationship between obesity-induced inflammation triggering endothelial dysfunction and the initiation of atherosclerosis development - Richard L. Jayaraj; Elhadi H Aburawi (Heart Vessels and Transplantation)
Obesity is a multifactorial, chronic inflammatory illness that affects individuals of all ages; it is linked to several cardiovascular and metabolic syndromes. Excessive accumulation of fat that impairs metabolic processes is a key feature of obesity. Globally, more than 1.9 billion adults are overweight or obese, and the number of people affected by obesity is increasing. Obesity contributes to cardiovascular disease (CVD) and metabolic disease (MD) through processes such as inflammation, hyperglycemia, and dyslipidemia, as well as metabolic syndrome and obstructive sleep apnea. Furthermore, alterations in adipose tissue composition in obesity play a major role in the production of inflammatory cytokines that promote endothelial dysfunction (ED). Endothelial dysfunction is the first step in the mechanisms underlying obesity-related complications, such as atherosclerosis, which is a major complication of obesity. A growing body of evidence suggests that obesity-related ED makes a significant contribution to the development of CVD and MD. Several mechanisms explain the association between obesity and atherosclerosis. The aim of this review is to summarize the effects of obesity-related inflammation on ED and its progression to atherosclerosis, focusing on cellular senescence, vascular aging, epigenetic modifications, reactive oxygen species, vascular calcification, and gut microbiota. In addition, we are also exploring new therapeutic strategies to reverse ED to prevent CVD and MD. Therefore, understanding the mechanisms underlying obesity-induced ED and its effects on atherosclerosis is crucial for developing therapeutic interventions.